Factors Related to the Quality of Antenatal Care Based on The Complete Scope of the Examination of Pregnant Women in the Health Center at Palopo City - Dian Furqani; Nuraerni Semagga (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
This study aims to see the factors that influence the quality of Antenatal Care in the City of Palopo; the type of design used is analytical descriptive with the Cross-Sectional Study approach. Samples from this study were all pregnant women based on 1, 2 and 3th-trimester pregnancy age, and 3 who were lived at the research location as many as 154 people who conducted inspection visits from January to March 2018. The results showed that the average age of the mother was 20 years. In the research statisticallly interconnected variables are maternal knowledge showed p-value (0.000). There are several variables have statistical significance, but there are differences in the percentage between the classification of each variabels as for the quality of Antenatal care associated with parity, maternal characteristics (age, education and occupation), antenatal care in each of the 1.2 trimester, and 3. Service access and economic welfare status, where each variable has a p-value> 0.005. The study expects that a health program should not look the quantity of maternal pregnancy visits, but pay attention to the examination checks received at each gestational age. We hope to encourage mothers to be more active in paying attention to the examinations that will be accepted based on their gestational age so that good health services and of recipients of services occur.